dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Karya Indah Multiguna Bekasi - rustomo (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Companies that produce quality goods in the form of corrugated cardboard boxes, PT Karya Indah Multiguna Bekasi City must pay attention to the accuracy of production results specifically in the Production planning and control section. This research examines the impact of a Kaizen culture and a sustainable work environment. Kaizen is a Japanese culture means continuous improvement and improvement of the quality of the workplace or work environment. This culture has been adopte by many Japanese companies around the world, especially manufacturing companies. Understanding of the kaizen culture and the use of English in companies is very important to serve as a knowledge provider in the world of work. Lack of understanding of this can lead to wrong attitudes, behaviors and interpretations in the corporate workplace. With a descriptive quantitative method to explain the relationship and influence of the two independent variables on the dependent variable. The research instrument with a questionnaire on the linket scale was give to 66 employees as respondents. The results of research on the process of implementing a culture of continuous improvement or kaizen and the work environment, with the 5S concept as its core. The data are state to be valid and reliable and partially the kaizen culture and work environment are jointly state to be significant to the performance of PT Karya Indah Multiguna Bekasi City, with the contribution of two independent variables to the dependent variable being very good.